Health journalism: Health reporting status and challenges - Mahrokh Keshvari; Niko Yamani; Peyman Adibi; Hossein Shahnazi (Wolters Kluwer Medknow Publications, 2018)
Background: Media play crucial role in disseminating health information. Due to the importance of accurate health news reports, and the national need to professionalism in health journalism, this study aimed to investigate the characteristics of health journalists, and health reporting status and the challenges involved. Materials and Methods: Using consensus sampling, this descriptive cross-sectional study was conducted on all health news reporters in Isfahan (34 journalists) in 2015-2016. Data collection was done via a researcher-made questionnaire. Content validity of the questionnaire was determined by qualitative method and based on the opinions of six experts. The test-retest reliability coefficient was 98.0. Data analysis was done by Statistical Package for the Social Sciences, version 16 and descriptive statistics and content analysis were used for analyzing the responses to two open questions. Results: Among 34 journalists, 56% were women and 44% men; the majority of journalists (65%) had no specialized training on health reporting, 35% of journalists were not able to understand the health issues, and the knowledge of medical terminology in 59% of them was moderate to low. The most important required skill for reporters was the ability to interpret medical research reports (88%), 97% were eager to participate in specialized health education. Conclusions: Our study showed that health journalists lacked knowledge and specialized training for dissemination of health news. This has brought about serious challenges. Thus, development and implementation of training courses in close collaboration with educational department of the Ministry of Health and news programs professionals at Islamic Republic of Iran Broadcasting is highly recommended.